A modified WPU coating and its preparation method and antibacterial application

By blending the PVP-modified Ag nanoparticle solution with WPU coating and forming a uniform WPU coating by spin coating or scraping method, the problem of full filling and stable release of Ag nanoparticles in the WPU matrix is ​​solved, and efficient antibacterial effect is achieved, and the bactericidal rate of Staphylococcus aureus and E. coli reaches more than 99.99%.

CN116987436BActive Publication Date: 2025-03-25NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311183949.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-25
Estimated Expiration
2043-09-14

AI Technical Summary

Technical Problem

In the prior art, when using Ag nanoparticles to fill WPU coatings, it is difficult to achieve full filling and stable release of Ag nanoparticles in the WPU matrix, which poses problems with security risks and complex impacts of antibacterial effects.

Method used

Full filling and stable release of Ag nanoparticles are achieved by blending the polyvinylpyrrolidone PVP-modified Ag nanoparticles with WPU coating and forming a uniform WPU coating by spin coating or scraping.

Benefits of technology

This method simplifies the loading process of Ag nanoparticles, improves the filling amount and stability of Ag nanoparticles in WPU coatings, and prepares a long-term effective WPU antibacterial coating, and the bactericidal rate of Staphylococcus aureus and E. coli reaches more than 99.99%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116987436B_ABST
    Figure CN116987436B_ABST
Patent Text Reader

Abstract

The present invention provides a modified WPU coating and a preparation method thereof and an application thereof in antibacterial aspects, belonging to the field of building materials. The present invention blends a PVP-modified Ag nanoparticle solution with a WPU coating, and the good compatibility between PVP and the WPU polymer matrix effectively promotes the full filling of Ag nanoparticles in the WPU coating, so that the WPU coating has excellent antibacterial properties. The modified WPU coating has good antibacterial properties, and the sterilization rates of Staphylococcus aureus and Escherichia coli are both above 99.99%; a WPU coating with uniform texture is formed in a room temperature environment by a spin coating or a scraping coating method; this process is quick and simple, effectively avoiding the complex and cumbersome Ag nanoparticle loading process, and greatly improving the filling amount and stability of Ag nanoparticles in the WPU coating, thereby preparing a long-term and effective WPU antibacterial coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a modified WPU coating, a preparation method thereof and an antibacterial application thereof. Background Art

[0002] Waterborne polyurethane (WPU) is considered as a potential coating on different substrates such as glass, paper, leather, metal and polymer materials. However, WPU has poor water resistance and is easily affected by microorganisms such as bacteria and fungi in humid environments. In order to improve the antibacterial properties of WPU coatings, some researchers have modified WPU with nanofillers and achieved great improvements in antibacterial properties. Rad and colleagues found that essential oils (RO) from prickly pear and rhizomes can improve the antibacterial properties of WPU.

[0003] The antimicrobial agents of WPU are mainly divided into organic antimicrobial agents and inorganic antimicrobial agents. The former mainly includes chitosan (CS), organic acids, ethanol, etc. Among them, chitosan, as a natural antimicrobial agent, is healthy and friendly to the environment and the human body. However, previous reports pointed out that the mechanical properties of CS are poor, which will have a complex effect on the antimicrobial effect. Organic acids and ethanol have good bactericidal properties, but there are potential environmental risks and safety hazards. In contrast, inorganic antimicrobial agents not only have excellent antibacterial properties, but also have good mechanical properties, so they have broad application prospects. At present, the more common inorganic antimicrobial agents mainly include Ag nanoparticles, Cu nanoparticles, high entropy alloy nanoparticles, and metal oxide nanoparticles. Thanks to the broad-spectrum antibacterial properties of Ag nanoparticles, an appropriate amount of Ag nanoparticles can be filled in WPU to significantly improve the antibacterial effect. Researchers have carried out a lot of work on this background.

[0004] In the process of filling Ag nanoparticles, two key factors are usually involved, namely the compatibility of Ag nanoparticles with the WPU matrix and the stability of the Ag nanoparticles after filling. The former determines the full filling of Ag nanoparticles in the WPU matrix, and the latter determines the stable existence of Ag nanoparticles in the system. However, the current process generally uses a more complicated method to complete the modification and protection of Ag nanoparticles, and there is a "burst" release behavior in the solution. The rapid release of Ag nanoparticles usually causes potential safety risks. How to quickly and efficiently achieve full filling and stable release of Ag nanoparticles in the WPU matrix has become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a modified WPU coating, a preparation method thereof and an application thereof in antibacterial aspects. From the perspective of antibacterial properties, the present invention blends a polyvinyl pyrrolidone (PVP)-modified Ag nanoparticle solution with a WPU coating, thereby giving the WPU coating excellent antibacterial properties. A WPU coating with a uniform texture is formed at room temperature by spin coating or scraping; this process is fast and simple, effectively avoiding the complex and tedious Ag nanoparticle loading process, greatly improving the filling amount and stability of Ag nanoparticles in the WPU coating, thereby preparing a long-term and effective WPU antibacterial coating.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A modified WPU coating is prepared by blending a PVP-modified Ag nanoparticle solution with a WPU coating.

[0008] The particle size of the PVP-modified Ag nanoparticles is 30-50 nm and they are evenly dispersed.

[0009] A method for preparing a modified WPU coating of the present invention comprises the following steps:

[0010] Step 1:

[0011] At room temperature, 15 to 25 g of PVP is added to 50 to 100 mL of a reducing agent and stirred for about 20 to 40 minutes until the PVP is completely dissolved, and then 2.4 to 3.2 g of AgNO3 is added and stirred until it is completely dissolved to obtain a mixed solution; the mixed solution is heated to 100 to 120° C., stirred at a constant temperature for 1 to 2 hours, and naturally cooled to room temperature to obtain a stock solution; acetone is added and centrifuged to extract ethylene glycol; and deionized water is used for centrifugation three times, and the upper clear liquid is discarded and 5 mL of deionized water is added to obtain a PVP-modified silver nanoparticle solution.

[0012] Step 2:

[0013] The PVP-modified Ag nanoparticle solution and the WPU coating are mixed and then ultrasonicated to obtain a modified WPU coating.

[0014] Furthermore, the reducing agent described in step 1 is an ethylene glycol solution; the volume ratio of the stock solution to acetone is 1:3 to 1:5; the centrifugal speed of adding acetone is 10000 to 12000 r / min; the time is 10 to 15 min; the volume ratio of the stock solution to deionized water is 1:1 to 1:3; the deionized water centrifugal speed is 5000 to 8000 r / min; the time is 5 to 10 min.

[0015] Furthermore, the volume ratio of the PVP-modified Ag nanoparticle solution to the WPU coating in step 2 is (0-3):(10-7), and after mixing, ultrasonic treatment is required at 100-300W for 3-5min.

[0016] Preferably, in step 2, the volume ratio of the PVP-modified Ag nanoparticle solution to the WPU coating is 3:7, and after mixing, ultrasonication is performed at 100 W for 3 minutes.

[0017] Furthermore, the antibacterial rate of the modified WPU coating against Escherichia coli reaches above 99.99%, and the antibacterial rate against Staphylococcus aureus reaches above 99.99%.

[0018] The modified WPU coating of the present invention is used in antibacterial aspects. The modified WPU coating is the original coating used for the WPU coating with antibacterial function.

[0019] Furthermore, the WPU coating with antibacterial function is obtained by uniformly coating the modified WPU coating on the substrate by scraping or spin coating, and drying in an oven at 40 to 60° C. for ≥1 hour.

[0020] Furthermore, when the substrate is a small-sized disc with a diameter of ≤40 mm or an area of ​​≤20×20 mm 2 When the substrate area is larger than 40×40mm, the coating is spread by spin coating. The first stage spin coating speed is 300-1000rpm, and the spin coating time is 10-15s. The second stage spin coating speed is 500-2000rpm, and the spin coating time is 20-25s. The coating amount is 20-25μL. When the substrate area is greater than 40×40mm 2 When the coating is spread by scraping, the volume of the absorbed coating is 150-200 μL, the scraping speed is 1-5 mm / s, the pad height is 100-200 μm, and the scraping temperature is room temperature.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention adopts a traditional Ag nanoparticle synthesis process, and the "one-pot method" quickly and efficiently realizes the preparation of Ag nanoparticle solution. Among them, PVP plays a dual role of modifying and protecting Ag nanoparticles. The effective modification of PVP can successfully achieve the uniform dispersion of Ag nanoparticles in the solution. In addition, thanks to the good compatibility between PVP and the WPU polymer matrix, it effectively promotes the full filling of Ag nanoparticles in the WPU coating, which plays a vital role in improving the antibacterial ability of the WPU coating.

[0023] 2. The PVP molecules in the present invention play a protective role in preventing the oxidation of Ag nanoparticles, which effectively avoids the premature oxidation of Ag nanoparticles in the environment and significantly curbs the + The massive production and "explosive" release in the solution ultimately greatly improve the biosafety of the modified WPU coating. On the other hand, since the side chain contains a large number of hydrophilic functional groups, the PVP molecule has a strong polarity, which will help the coating to produce a strong hydrogen bond and hydration layer in the water environment, thereby improving the hydrophilicity and antifouling ability of the WPU coating to a certain extent.

[0024] 3. Ag in the solution of the present invention + The reduction uses ethylene glycol as a reducing agent. Compared with highly toxic reducing agents such as hydrogen iodide (HI) and hydrazine (N2H4) used in traditional processes, ethylene glycol has lower biological toxicity and good reducing properties, which fully meets the current green, environmentally friendly, low-cost and sustainable development concept.

[0025] 4. The present invention adopts for the first time a modified WPU coating prepared by blending a PVP-modified Ag nanoparticle solution with a WPU coating. Compared with other cumbersome and complicated Ag nanoparticle loading processes, this process only requires directly mixing the PVP-modified Ag nanoparticle solution with the WPU coating to achieve sufficient filling of Ag nanoparticles, effectively avoiding the problem of Ag + The "explosive" release of Ag nanoparticles modified by PVP gradually increased with the gradual increase in the volume of the solution, and the C / O ratio of the system gradually increased. The contact angle of WPU gradually decreased from 91.82° to 71.02° after modification. + The release of the modified WPU coating is significantly improved. At the same time, the modified WPU coating has good antibacterial properties, and the sterilization rate against Staphylococcus aureus and Escherichia coli has reached more than 99.99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the sterilization of the modified WPU coating;

[0027] Figure 2 is a SEM image of the modified WPU coating prepared in Example 1;

[0028] Figure 3 is the EDS spectrum of the modified WPU coating prepared in Example 1;

[0029] Figure 4 The following are the C and O mass fraction histograms and C / O trend graphs in the unmodified WPU coating, the modified WPU coating prepared in Example 4, and the modified WPU coating prepared in Example 1;

[0030] Figure 5It is the infrared spectra of PVP raw material, unmodified WPU and modified WPU coating prepared in Example 1;

[0031] Figure 6 The variation trend of the surface contact angle of the WPU coating prepared in Example 3, Example 2, and Example 1 is shown in FIG.

[0032] Figure 7 Ag in the WPU coating prepared in Examples 1-4 + Release in PBS solution;

[0033] Figure 8 It is an unmodified WPU coating. The WPU coating prepared in Examples 1-4 is a plate image of attached bacteria after being immersed in 0.9% sodium chloride plus 0.5g / L yeast extract and 0.5g / L tryptone solution containing Staphylococcus aureus and Escherichia coli for 72h;

[0034] Fig. 9 It is an unmodified WPU coating. The WPU coating prepared in Examples 1-4 is a live-dead staining picture after being immersed in 0.9% sodium chloride plus 0.5g / L yeast extract and 0.5g / L tryptone solution containing Staphylococcus aureus and Escherichia coli for 72 hours. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with embodiments.

[0036] In the following examples, the antibacterial rate of Staphylococcus aureus in the modified WPU coating prepared by blending the PVP-modified Ag nanoparticle solution with the WPU coating was measured under the harsh conditions of adding 0.5 g / L yeast extract and 0.5 g / L tryptone to 0.9% sodium chloride solution, with an initial bacterial concentration of 10 6 CFU / mL, the antibacterial rate is the data after immersion for 72 hours.

[0037] In the following examples, the antibacterial rate of Escherichia coli in the modified WPU coating prepared by blending the PVP-modified Ag nanoparticle solution with the WPU coating was measured under the harsh conditions of adding 0.5 g / L yeast extract and 0.5 g / L tryptone to 0.9% sodium chloride solution, with an initial bacterial concentration of 10 6 CFU / mL, the antibacterial rate is the data after immersion for 72 hours.

[0038] In the following examples, unless otherwise specified, the raw materials and equipment used are commercially available.

[0039] Example 1

[0040] A method for preparing a modified WPU coating comprises the following steps:

[0041] Step 1:

[0042] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0043] Step 2:

[0044] The PVP-modified Ag nanoparticle solution and the WPU coating are mixed in a volume ratio of 3:7, and then ultrasonicated for 3 minutes at 100 W to obtain a modified WPU coating. The SEM image of the modified WPU coating is shown in FIG. Figure 2 As shown, the EDS spectrum of the modified WPU coating is as follows Figure 3 shown.

[0045] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0046] The modified WPU coating was evenly coated by spin coating. The rotation speed of the first stage was 600 rpm for 10 seconds, and the rotation speed of the second stage was 1000 rpm for 20 seconds. After the spin coating was completed, the modified WPU coating was dried by heating in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with antibacterial function, such as Figure 1 shown.

[0047] from Figure 2 It can be seen that the surface of the modified WPU coating after drying contains a large amount of Ag nanoparticles, and the Ag nanoparticles are evenly distributed with little agglomeration behavior; Figure 3 It can be seen that the main elements of the modified WPU coating are C, N, O, and Ag, among which the mass fraction of the Ag element is 1.26%.

[0048] Example 2

[0049] A method for preparing a modified WPU coating comprises the following steps:

[0050] Step 1:

[0051] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0052] Step 2:

[0053] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 2:8 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0054] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0055] The modified WPU coating was evenly coated by spin coating, wherein the rotation speed of the first stage was 600 rpm for 10 s, and the rotation speed of the second stage was 1000 rpm for 20 s; after the spin coating was completed, the modified WPU coating was dried by heating in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with antibacterial function.

[0056] Example 3

[0057] A method for preparing a modified WPU coating comprises the following steps:

[0058] Step 1:

[0059] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0060] Step 2:

[0061] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 1:9 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0062] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0063] The modified WPU coating was evenly coated by spin coating, wherein the rotation speed of the first stage was 600 rpm for 10 s, and the rotation speed of the second stage was 1000 rpm for 20 s; after the spin coating was completed, the modified WPU coating was dried by heating in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with antibacterial function.

[0064] Example 4

[0065] A method for preparing a modified WPU coating comprises the following steps:

[0066] Step 1:

[0067] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0068] Step 2:

[0069] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 1:19 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0070] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0071] The modified WPU coating was evenly coated by spin coating, wherein the rotation speed of the first stage was 600 rpm for 10 s, and the rotation speed of the second stage was 1000 rpm for 20 s; after the spin coating was completed, the modified WPU coating was dried by heating in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with antibacterial function.

[0072] Depend on Figure 4 It can be seen that with the gradual increase in the volume of PVP-modified Ag nanoparticle solution, the C / O ratio of the system increased significantly. Figure 5 The infrared absorption spectra of PVP, WPU and PVP / Ag-WPU-30% coatings are shown in Figure 2. Compared with WPU, the PVP / Ag-WPU-30% composite material has a higher absorption rate at 1656 cm -1 Infrared absorption peaks appear, and the composite material is at 1700-1600cm -1 The transmittance in this range is much lower than that of WPU coating, which is due to the carbonyl stretching vibration peak in the PVP molecule significantly enhancing the absorbance of the composite material in this range. Figure 7 Ag in the WPU coating prepared in Examples 1-4 + Release in PBS solution; Figure 6 It shows that with the increase of the volume fraction of Ag nanoparticle solution, the Ag + The release concentration increased significantly.

[0073] Example 5

[0074] A method for preparing a modified WPU coating comprises the following steps:

[0075] Step 1:

[0076] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0077] Step 2:

[0078] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 3:7 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0079] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0080] The modified WPU coating was evenly coated by spin coating, wherein the rotation speed of the first stage was 1000 rpm, the time was 10 s, and the rotation speed of the second stage was 2000 rpm, the time was 20 s; after the spin coating was completed, the modified WPU coating was dried in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with good antibacterial properties.

[0081] Example 6

[0082] A method for preparing a modified WPU coating comprises the following steps:

[0083] Step 1:

[0084] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0085] Step 2:

[0086] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 3:7 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0087] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 20μL;

[0088] The modified WPU coating was evenly coated by spin coating, wherein the rotation speed of the first stage was 300 rpm and the time was 10 s, and the rotation speed of the second stage was 500 rpm and the time was 20 s. After the spin coating was completed, the modified WPU coating was dried in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with good antibacterial properties.

[0089] Example 7

[0090] A method for preparing a modified WPU coating comprises the following steps:

[0091] Step 1:

[0092] At room temperature, 20g of PVP was added to 75mL of ethylene glycol and stirred for about 30min until PVP was completely dissolved, and the solution was light yellow at this time; 3.2g of AgNO3 was added to the mixed solution and stirred until it was completely dissolved to obtain a mixed solution, which was dark brown; the mixed solution was heated to 120°C, stirred at a constant temperature for 1h, and naturally cooled to room temperature to obtain a stock solution; acetone was added for centrifugation, and the volume ratio of the stock solution to acetone was 1:3; the centrifugal speed was 10000r / min, the time was 15min, and ethylene glycol was extracted; deionized water was used for centrifugation three times, and the volume ratio of the stock solution to deionized water was 1:1; the centrifugal speed was 5000r / min, the time was 10min, and 5mL of deionized water was added after the supernatant was poured out to obtain a PVP-modified silver nanoparticle solution, whose average particle size was about 50nm and was evenly dispersed.

[0093] Step 2:

[0094] The PVP-modified Ag nanoparticle solution and the WPU coating were mixed in a volume ratio of 3:7 and subjected to ultrasound at 100 W for 3 min to obtain the modified WPU coating.

[0095] The modified WPU coating of the present invention is applied to the surface of a substrate material. The substrate material used in this embodiment is 316L stainless steel, and the stainless steel specification is 1×1 cm 2 ; Among them, the volume of the absorbed coating is 200μL;

[0096] The modified WPU coating was evenly coated by scraping; the process parameters of scraping were: scraping speed 1 mm / s, gasket height: 100 μm, scraping temperature: room temperature; after scraping, the modified WPU coating was dried in an oven at 40°C for ≥1h, thereby preparing a modified WPU coating with good antifouling and antibacterial properties.

[0097] Control group 1

[0098] 316L stainless steel coated with WPU coating.

[0099] Control group 2

[0100] The antibacterial modified WPU coating (HNT / Ag-WPU) was prepared by blending a halite-modified Ag nanoparticle solution with WPU coating.

[0101] Control group 3

[0102] The antibacterial modified WPU coating (CNNs / Ag-WPU) was prepared by blending Ag nanoparticle solution modified with WPU coating.

[0103] Comparative Example 1

[0104] A method for preparing a modified WPU coating is the same as that in Example 1, except that:

[0105] In the prepared antifouling and antibacterial modified WPU, the volume ratio of Ag nanoparticle solution to WPU coating is 1:99; since the volume proportion of the mixed Ag nanoparticle solution is too small, there is no significant difference in the contact angle between PVP / Ag-WPU-1% coating and WPU coating, and the antibacterial performance of the modified PVP / Ag-WPU-1% did not reach the expected value.

[0106] Comparative Example 2

[0107] A method for preparing a modified WPU coating is the same as that in Example 1, except that:

[0108] Spin coating was used, where the first stage was 100 rpm for 10 seconds, and the second stage was 250 rpm for 20 seconds. After the spin coating was completed, the modified WPU coating was dried in an oven at 40°C for ≥1 hour. Due to the slow rotation speed, a large amount of WPU coating remained on the surface of the substrate, and the formed WPU coating failed to form a uniform film.

[0109] Comparative Example 3

[0110] A method for preparing a modified WPU coating is the same as that in Example 1, except that:

[0111] Spin coating was used, where the first stage was 2000 rpm for 10 seconds, and the second stage was 4000 rpm for 20 seconds. After the spin coating was completed, the modified WPU coating was dried in an oven at 40°C for ≥1h. Due to the high speed, there was too little WPU coating on the substrate surface, and the performance of the formed WPU coating film was greatly reduced.

[0112] Verification Example

[0113] The antibacterial effect of the modified WPU coating prepared in the above embodiment was verified as follows. The specific implementation method is as follows: plate counting method, confocal live-dead staining observation, and the specific implementation process is as follows:

[0114] 1. Plate count method

[0115] Test bacteria: Staphylococcus aureus, Escherichia coli

[0116] The detection method is as follows:

[0117] (1) The WPU coatings of control groups 1-3 were used as control group samples; the antibacterial modified WPU coatings prepared in Examples 1-4 were used as experimental group samples;

[0118] (2) The test group and control group samples (three samples in each group) were cultured with common Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) in a 0.9% sodium chloride solution containing 0.5 g / L yeast extract and 0.5 g / L tryptone at a constant temperature and humidity for 72 hours; the bacteria adhering to the coating surface were shaken off into 1 mL PBS buffer using a vortex instrument, and 100 μl of the bacterial solution was taken for counting. The initial bacterial concentration was controlled to be 10 6 CFU / mL;

[0119] The antibacterial rate (%) of different experimental examples against two bacteria (Staphylococcus aureus and Escherichia coli) was calculated according to the following formula:

[0120] Antibacterial rate (%) = [(number of live bacteria on the surface of sample 1 in control group - number of live bacteria on the surface of antibacterial modified WPU coating) / number of live bacteria on the surface of sample 1 in control group] × 100%,

[0121] Figure 8 The unmodified WPU coating, the WPU coating prepared in Examples 1-4, and the flat plate coating results of the five coatings after being immersed in 0.9% sodium chloride plus 0.5g / L yeast extract and 0.5g / L tryptone solution containing Staphylococcus aureus and Escherichia coli for 72 hours. It can be seen from the number of colonies on the plate that as the volume content of the Ag nanoparticle solution gradually increases, the number of live bacteria on the coating surface gradually decreases. According to the calculation formula of the antibacterial rate, it can be calculated that the antibacterial rates of the WPU coatings prepared in Examples 1-4 against Staphylococcus aureus are 99.99%, 99.38%, 98.10%, and 91.95%, respectively; the antibacterial rates against Escherichia coli are 99.99%, 99.65%, 93.98%, and 63.98%, respectively. Table 1 shows the antibacterial rate (%) data of the three coatings in Control Group 2, Control Group 3, and Example 1 against Staphylococcus aureus and Escherichia coli (the antibacterial rate data of HNT / Ag-WPU and CNNs / Ag-WPU are from the literature). The antibacterial rates of the coatings in Control Group 2, Control Group 3, and Example 1 against Staphylococcus aureus were 76.4%, 91.82%, and 99.99%, respectively; the antibacterial rates against Escherichia coli were 99.99%, 99.4%, and 99.99%, respectively. By comparison, it is known that PVP / Ag-WPU has the best antibacterial performance against both Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli), which strongly confirms the broad-spectrum antibacterial property of this process.

[0122] Table 1: Test results of the antibacterial properties of the three coatings in control group 2, control group 3, and Example 1 against Staphylococcus aureus

[0123] HNT / Ag-WPU CNNs / Ag-WPU PVP / Ag-WPU Staphylococcus aureus 76.4% 91.82% 99.99% Escherichia coli 99.99% 99.4% 99.99%

[0124] Table 1

[0125] 2. Confocal live-dead staining images

[0126] Fig. 9 The WPU coatings prepared in Examples 1-4 are unmodified WPU coatings, and the five coatings are immersed in 0.9% sodium chloride plus 0.5g / L yeast extract and 0.5g / L tryptone solution containing Staphylococcus aureus and Escherichia coli for 72 hours, and the live and dead staining pictures of attached bacteria are shown. From the changes in the red and green color distribution in the live and dead staining pictures, it can be seen that with the gradual increase in the volume content of the Ag nanoparticle solution, the number of live bacteria attached to the coating surface gradually decreases, and the number of dead bacteria also decreases significantly, which fully demonstrates that the Ag nanoparticle solution not only has a high-efficiency and broad-spectrum antibacterial efficiency against bacteria, but also significantly reduces the adhesion behavior of bacteria, effectively avoiding the formation of bacterial biofilms.

[0127] The above embodiments are only for explaining the technical solutions of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified WPU coating, characterized in that: The modified WPU coating is prepared by blending a solution of Ag nanoparticles modified by polyvinyl pyrrolidone (PVP) with a waterborne polyurethane WPU coating; the particle size of the Ag nanoparticles modified by PVP is 30-50 nm and is evenly dispersed; The following steps are involved: Step 1: At room temperature, 15-25 g of PVP is added to 50-100 mL of reducing agent and stirred for 20-40 min until PVP is completely dissolved, and then 2.4-3.2 g of AgNO3 is added and stirred until it is completely dissolved to obtain a mixed solution; the mixed solution is heated to 100-120° C., stirred at a constant temperature for 1-2 h, and naturally cooled to room temperature to obtain a stock solution; acetone is added and centrifuged to extract ethylene glycol; deionized water is used for centrifugation three times, and the supernatant is discarded and 5 mL of deionized water is added to obtain a PVP-modified silver nanoparticle solution; Step 2: The PVP-modified Ag nanoparticle solution and the WPU coating are mixed and then ultrasonicated to obtain a modified WPU coating.

2. The preparation method of the modified WPU coating according to claim 1, characterized in that: The reducing agent described in step 1 is ethylene glycol solution; the volume ratio of the stock solution to acetone is 1:3~1:5; the centrifugal speed of adding acetone is 10000~12000 r / min; the time is 10~15 min; the volume ratio of the stock solution to deionized water is 1:1~1:3; the deionized water centrifugal speed is 5000~8000 r / min; the time is 5~10 min.

3. The preparation method of the modified WPU coating according to claim 1, characterized in that, In step 2, the volume ratio of the PVP-modified Ag nanoparticle solution to the WPU coating is (0-3): (10-7). After mixing, ultrasonic treatment is required at 100-300 W for 3-5 min.

4. The preparation method of the modified WPU coating according to claim 1, characterized in that: In step 2, the volume ratio of the PVP-modified Ag nanoparticle solution to the WPU coating is 3:

7. After mixing, ultrasonic treatment is performed at 100 W for 3 min.

5. The preparation method of the modified WPU coating according to claim 1, characterized in that, The modified WPU coating has an antibacterial rate of more than 99.99% against Escherichia coli, and an antibacterial rate of more than 99.99% against Staphylococcus aureus.

6. An application of the modified WPU coating according to any one of claims 1 to 5 in antibacterial applications, characterized in that: The modified WPU coating is used as the original coating of the WPU coating with antibacterial function.

7. The use of the modified WPU coating in antibacterial aspects according to claim 6, characterized in that: The WPU coating with antibacterial function is obtained by uniformly coating the modified WPU coating on a substrate by scraping or spin coating, and drying in an oven at 40-60° C. for ≥1 hour.

8. The use of the modified WPU coating according to claim 7 in antibacterial aspects, characterized in that: When the substrate is a small-sized disc with a diameter of ≤40 mm or an area of ​​≤20×20 mm 2 When the substrate area is larger than 4×4mm, the coating is spread by spin coating. The first stage spin coating speed is 300~1000 rpm, the spin coating time is 10~15 s; the second stage spin coating speed is 500~2000 rpm, the spin coating time is 20~25 s, and the coating amount is 20~25 μL. When the substrate area is greater than 4×4mm 2 When the coating is spread by scraping, the volume of the absorbed coating is 150-200 μL, the scraping speed is 1-5 mm / s, the pad height is 100-200 μm, and the scraping temperature is room temperature.

Citation Information

Patent Citations

  • Preparation method of water-based nano-silver / fluorocarbon anti-bacteria coating

    CN103642355A

  • High-transparency antibacterial coating as well as preparation method and application thereof

    CN114806371A

  • Removable, waterproof multi-layer coating having antibacterial properties for contact surfaces and method for the preparation thereof

    US20240081334A1